SPATIO-TEMPORAL TRENDS IN THE PHYSICOCHEMICAL PARAMETERS OF MID-LAGOS LAGOON WATER, SOUTH-WESTERN NIGERIA - OLUWAJOBA , E.O; IKEWENWEI, N.B; ABDUL, W.O; IDOWU , A.B; POPOOLA , S.O (Nigerian Journal of Fisheries, 2022)
The spatio-temporal distributions of physicochemical properties of Mid-Lagos Lagoon water, South-western Nigeria were investigated by the division of the stations into three zones of 10km interval (Zones 1, 2 and 3) between January 2014 and December 2015. The observed ranges of physicochemical characteristics from the study area were: dissolved oxygen 3.2-7.1mg/L; pH: 6.6-8.5; temperature: 27.39-32°C; electrical conductivity: 11.06-51.46 μS/cm; salinity: 0.22-33.87ppt; turbidity: 27.09-32.71NTU. The nitrate and phosphate concentrations ranged from 0.08-1.71mg/L and 0.02-3.9mg/L respectively. The pH and temperature were within the desired values for healthy marine ecosystems when compared with the Federal Ministry of Environment (FMENV) Nigeria and World Health Organization permissible limits (pH:6.5-9 and temperature<40°C). Zone-1 had the highest pH, dissolved oxygen, electrical conductivity, salinity, nitrate and phosphate values, and lowest turbidity level. These values implied enhanced water quality at Zone-1, compared to Zones-2 and which reflected in the higher productivity at Zone 1 compared to Zones-2 and 3 respectively.